"Everything Is Connected": Health Lifestyles and Teenagers' Social Distancing Behaviors in the COVID-19 Pandemic. (October 2021) - Mollborn, Stefanie; Mercer, Katie Holstein; Edwards-Capen, Theresa
Social distancing during the COVID-19 pandemic requires people to engage in new health behaviors that are public, monitored, and often contested. Parents are typically considered responsible for controlling their children's behavior and instilling norms. We investigated how parents and teens managed teenagers' social distancing behaviors. Analyzing longitudinal (2015–2020), dyadic qualitative interviews with teenagers and their parents in 20 families from two middle-class communities in which social distancing was normative, we found that preexisting health lifestyles were used to link social distancing behaviors to specific identities, norms, and understandings of health. The pandemic presented challenges resulting from contradictory threats to health, differing preferences, and conflicting social judgments. Parents responded to challenges by adhering to community norms and enforcing teens' social distancing behaviors. They drew on preexisting, individualized health lifestyles as cultural tools to justify social distancing messages, emphasizing group distinctions, morality, and worth in ways that perpetuated inequalities.